2012
DOI: 10.1299/kikaia.78.646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Local Mechanical Properties of High Strength Steels by Indentation Method

Abstract: High strength steels are used for various important components such as rolling bearings to ensure safety. Strength designs for these components require material properties at the local areas. The objective of the present study is to evaluate the local mechanical properties of high strength steels by the dual-indenter method. Non-dimensional Π function is developed for 118 degree trigonal pyramid indenter using finite-element method. Dual-indenter method is conducted by indenters with the apex angles of 115 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Many studies using the indentation method have been reported (Nakashima et al, 2016;Yonezu et al, 2006;Sakaue et al, 2012). The local stress-strain relationship can be evaluated using the multi-indentation method, which is performed by indentation with multiple apex angles (Ozeki et al, 2014;Komori et al, 2012). However, numerous indentation studies have reported an increase in the hardness with decreasing depth of penetration, which is known as the indentation size effect.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using the indentation method have been reported (Nakashima et al, 2016;Yonezu et al, 2006;Sakaue et al, 2012). The local stress-strain relationship can be evaluated using the multi-indentation method, which is performed by indentation with multiple apex angles (Ozeki et al, 2014;Komori et al, 2012). However, numerous indentation studies have reported an increase in the hardness with decreasing depth of penetration, which is known as the indentation size effect.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using the indentation method have been reported (Nakashima et al, 2016;Yonedu et al, 2006;Sakaue et al, 2012). The local stress-strain relationship can be evaluated using the multi-indentation method, which is performed by indentation with multiple apex angles (Ozeki et al, 2014;Komori et al, 2012). However, numerous indentation studies have reported an increase in the hardness with decreasing penetration depth, which is known as the indentation size effect.…”
Section: Introductionmentioning
confidence: 99%